FEATURES OF THE USE OF MOBILE COMMUNICATION IN THE STUDENT ENVIRONMENT / ОСОБЕННОСТИ ИСПОЛЬЗОВАНИЯ МОБИЛЬНОЙ СВЯЗИ В СТУДЕНЧЕСКОЙ СРЕДЕ - SHARIKOV ALEXANDER V . / ШАРИКОВ А.В.; EROFEEV SERGEI V. / ЕРОФЕЕВ С.В. (Наука телевидения, 2019)
The article discusses the features of mobile communication in the student environment in the context of socio-cultural transformations generated by technological progress. In the first part of the article the authors briefly describe the history of mobile communication. Trends in sociohumanitarian research in the 20th—21st centuries with the emergence and widespread use of new electronic means of communication—radio, television, Internet, mobile communication—are also briefly considered. In all cases, four stages of socio-cultural adaptation of information and communication innovations in relationship with young people are mentioned: 1) attempts to understand new media as a means of learning; 2) detection and study of problem areas created by new media in relations with the young generation; 3) development of “counteractions” against arising negative phenomenon at the level of the introduction of legal norms and attempts to organize ethical self-regulation of new branches in the media industry; 4) introduction of aspects of “new literacy” as elements of education in terms of information literacy, media literacy, digital literacy, mobile literacy, etc. The second part of the article presents some data of sociological studies, which clarify the features of the use of mobile communication by Russian students, in particular, using a smartphone. Data from three surveys conducted in 2018 are analyzed—the study of the company “Mediascope”, as well as surveys of students from two Moscow universities—GITR and HSE. Surveys have shown that the use of mobile communication among Russian students is close to 100%, and the scale of use of smartphones is much higher than simple mobile phones: according to “Mediascope”, 91.3% of students have smartphones and only 6.9% use mobile phones without access to the Internet. Among the respondents of GITR and HSE, 100% of the students had smartphones. The use of mobile communication by Russian students is characterized by wide functionality—the total number of identified functions amounted to more than 20, most of which are related to the Internet. The intensity of inclusion in information and communication processes varies significantly between students who have a smartphone and those who do not. Students who own smartphones are much more active in using the Internet. According to “Mediascope”, the percentage of those who used the Internet, in all the marked functional positions, was higher than among those who used simple mobile phones. The biggest difference is in visiting social media (73.8% vs. 40.6%), listening to and downloading music (48.6% vs. 19.3%), viewing and uploading photos (48.5% vs. 20.1%), watching and downloading videos (42.5% vs. 23.7%), and playing games (24.0% vs. 9.1%). It is concluded that the use of mobile Internet contributes to the further strengthening of the audiovisual component of mass culture.